Validation of the Global Diet Quality Score (GDQS) among children 10 to 14 years of age - Batis, Carolina; Castellanos-Gutiérrez, Analí; Ali, Nazia Binte; Arsenault, Joanne E.; Atayde, Agata M. P.; Bromage, Sabri; Deitchler, Megan; Diop, Loty; Gelli, Aulo; Kehoe, Sarah H.; Leonardo, Sofia; Moursi, Mourad; et al. (Oxford University Press, 2025)
Objective We aimed to evaluate the performance of the Global Diet Quality Score (GDQS) in predicting nutrient intake and health outcomes among children aged 10–14 years old in Mexico, the United States, the United Kingdom, and China. For comparison, we evaluated other dietary metrics (Minimum Dietary Diversity for Women [MDD-W], the Global Dietary Recommendations score [GDR], and the Healthy Eating Index–2020 [HEI-2020]).